Narrative Review of Free Radicals and Reactive Oxygen Species in Otitis Media - Jeongmin Lee; Seok Min Hong; Yong Sung Choi; Jinseok Lee; Joon Hyung Yeo; Sung Soo Kim; Jae Min Lee; Dong Keon Yon; Seung Geun Yeo (Antioxidants)
Many studies have evaluated the roles of free radicals and reactive oxygen species (ROS) in various diseases. To date, however, no systematic review has specifically investigated the involvement of free radicals and ROS in acute otitis media (OM), OM with effusion, and chronic OM. The present study therefore assessed the roles of free radicals and ROS in OM. SCOPUS, PubMed, Cochrane Library, EMBASE, and Google Scholar were comprehensively searched to identify studies assessing the roles of free radicals and ROS in OM. Relevant studies were identified and their findings summarized. The literature search identified 21 studies. A review of their findings showed that the concentrations of hydrogen peroxide (H2O2), lipid hydroperoxide (LPO), and myeloperoxidase (MPO) were elevated in patients with acute OM; that the concentrations of H2O2, LPO, MPO, xanthine oxidase (XO), superoxide dismutase (SOD), glutathione peroxidase (GPX), malondialdehyde (MDA), hydroxyl radical (·OH), and nitrotyrosine were elevated in patients with OM with effusion; and that the levels of nitric oxide (NO), MPO, 4-hydroxynonenal (4-HNE), and malondialdehyde (MDA) were elevated in patients with chronic OM. Although some studies reported that SOD levels were increased in patients with OM with effusion, decreases in antioxidants such as SOD and catalase, as well as total antioxidant capacity, were observed across all types of OM. Although the levels of free radicals and ROS varied by type of OM, study design, control group selection, sample type, ROS and free radical markers, and antioxidant types, most studies showed increased ROS and decreased antioxidants in OM patients. These findings suggest that levels of free radicals and ROS are strongly associated with the pathophysiology of OM.